Evaluation of Sales Accounting Information Systems in Controlling Credit Risk - Sariyanto; Renny Lubis; Ruri Aditya Sari; Iswandi Idris (SEAN Institute, 2023)
The formulation of the problem in this research is whether the sales accounting information system can recognize credit risk at PT. UBM. The objective is to determine the role of the accounting information system in controlling credit risk. This research is a descriptive qualitative research to find out the accounting information system that plays a role in identifying credit risk at PT. UBM. By using primary and secondary data, the data is processed through qualitative data. In achieving the objectives of the document internal control system used by PT. UBM is related to the Sales Accounting Information System consisting of goods orders, minutes of receipt and delivery of goods, and sales invoices. Then record the sales accounting information system at PT. UBM consists of sales journal, cash receipts journal, general ledger, inventory card and warehouse card. While the functions related to the sales accounting information system at PT. UBM is a sales function, accounting function, warehouse function, shipping function, accounts receivable function and billing function and finally the Standard Operating Procedure at PT. UBM consists of sales procedures, procedures for sending goods to consumers, procedures for receivables and procedures for receiving money. Judging from the documents, records, functions involved in the sales accounting information system and sales standard operating procedures at PT. UBM is complete and well covered.